Strategi Pengelolaan Potensi Pariwisata dalam Meningkatkan Kunjungan Wisatawan di Kota Semarang - Yuniarso, Rizky; Mustam, Mochammad; Rihandoyo, Rihandoyo (Journal of Public Policy and Management Review, 2014)
Semarang city has some interesting potential to make tourist attraction for the tourists visiting Semarang. Although it has a lot of potential for tourism, tourists and investors are reluctant glances as less attractive. Though Semarang is a transit city that is developing themselves to a tourist town. The problem is then to be observed is how do tourism management strategy Disbudpar the city, then the factors supporting and inhibiting factors what is in the implementation of these strategies. And whether the strategy is done is right or not.The purpose of the research conducted is to describe the management strategies that do Disbudpar and identify factors driving and inhibiting factors in the implementation of strategy. Then propose appropriate management strategies for Disbudpar. The method used in this study uses descriptive qualitative. The theory used in this study is strategic management and tourism management. Then identify strategic issues that exist using SWOT analysis, and determining the issues considered strategic by using a litmus test assessment.From the research that has been done, there are twelve strategic issues that arise through the assessment using SWOT analysis. Then, after a litmus test assessed, there are four proposed strategies in the management of tourism in the city of Semarang them improve coordination among agencies in order to attract investors in the field of tourism, promote cooperation and good communication pattern between the government and the community, improving the quality and quantity of tourist guides to develop Semarang tourist attraction, as well as improving the implementation of existing programs to enhance the preservation of culture typical of Semarang.